2020
DOI: 10.1021/acs.analchem.0c03431
|View full text |Cite
|
Sign up to set email alerts
|

Multicollector Inductively Coupled Plasma–Mass Spectrometry with 1013 Ω Faraday Cup Amplifiers for Ultrasensitive Mg Isotopic Analysis of Cerebrospinal Fluid Microsamples

Abstract: Magnesium isotopic analysis of cerebrospinal fluid (CSF) is a potentially interesting approach for studies on neurodegeneration. However, this type of analysis is challenging because of the invasiveness of the sampling and small sample volume. In this work, a novel analytical method was developed for ultrasensitive Mg isotopic analysis of CSF microsamples via multicollector inductively coupled plasma−mass spectrometry (MC-ICP-MS) using high-gain 10 13 Ω Faraday cup amplifiers. The intermediate and internal err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Measurement of Mg isotopes in cerebrospinal fluid is challenging due to the invasive nature of the procedure, but has potential uses in studies of neurodegeneration. Grigoryan et al 176 used 10 13 Ω amplifiers with MC-ICP-MS to reduce errors on the micro sample determinations of small amounts of Mg (between 7 and 10 μg L −1 ). The ∂Mg values were found to be similar to the ratios determined for 150 μg L −1 samples.…”
Section: Isotope Analysismentioning
confidence: 99%
“…Measurement of Mg isotopes in cerebrospinal fluid is challenging due to the invasive nature of the procedure, but has potential uses in studies of neurodegeneration. Grigoryan et al 176 used 10 13 Ω amplifiers with MC-ICP-MS to reduce errors on the micro sample determinations of small amounts of Mg (between 7 and 10 μg L −1 ). The ∂Mg values were found to be similar to the ratios determined for 150 μg L −1 samples.…”
Section: Isotope Analysismentioning
confidence: 99%
“…Accurate and precise Mg isotope ratios could be achieved using about 5 mL of human CSF. 12 The method was applied for CSF collection from hydrocephalus patients. The other publication refers to the isotopic determination of Cu and Zn in patients with amyotrophic lateral sclerosis or Alzheimer's disease.…”
Section: Biological Uids Requiring Invasive Sample Collectionmentioning
confidence: 99%
“…It is well known that a low amount of sample and/or a low target isotope concentration can strongly compromise applications focused on high-precision isotopic analysis of biouids by MC-ICP-MS. 11 The use of aerosol desolvating systems, high-efficiency jet interfaces, high gain Faraday cup ampliers (10 13 U with respect to the 10 11 U conventional ones) and ion counter devices has proved to enhance instrument sensitivity. 12,13 Methods based on sample mixing of the analyte with a non-enriched in-house standard, 11 the use of droplets of serum deposited on silicon, 14 or preconcentration procedures, 15 have been proposed to extend the applications of MC-ICP-MS within a clinical context.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium isotopic analysis of human tissues is a fledging field with the Mg isotopic composition showing potential to be applied as a biomarker in clinical settings (Grigoryan et al, 2019(Grigoryan et al, , 2020b(Grigoryan et al, , 2021. To the best of the authors' knowledge, no studies have reported δ 26 Mg values for hair or nails.…”
Section: Introductionmentioning
confidence: 99%